Exploring Leadership Competencies For Crisis Management: A Study In The Retail Industry In Sarawak - Priscella, Ambrose (Universiti Malaysia Sarawak, (UNIMAS), 2021)
Leaders especially the management lines in the organization are the important people in keeping the organization to keep survive and thrive during this COVID-19 pandemic. Through this study, the challenges faced by the leaders during this pandemic will be explored, the strategies used to overcome the challenges will be discovered and the important leadership competencies in managing crisis are identified. This study aims to add literature review on crisis management for local level (Sarawak, Malaysia) in retail industry. The research is using qualitative design to discover new insights on crisis management. Therefore, case study design is chosen as the approach. 8 informants who hold position in managerial from retail industry in Sarawak area were interviewed in the in-depth interview via phone calls and Zoom Meeting in June 2021. The data that has been collected were analyzed by using content analysis where the keywords, phrases and sentences were grouped into themes and category. The findings found that leaders are facing with the challenges such as in financial aspect, health and well-being, struggling for sustainability of the company and managing human resource. Therefore, the strategies used are focusing on the employees focus, business strategy and safety strategy. Apart from that, the findings also highlighted that leaders must possess competencies such as able to control emotion, communication skills, problem solving skills and ability to influence. At the end, this study is expected to contribute the insights on managing the VIII crisis effectively to the organizations, human resource practitioners and future research in Malaysia to prepare the strategic human resource development and management for facing the uncertainty